Efektivitas Model Project Based Learning (PjBL) terhadap Kreativitas Siswa dalam Mengembangkan Inovasi Pembelajaran Matematika - Ratna Yulis Tyaningsih (Pendidikan Matematika FKIP Universitas Mataram, 2022)
Creativity is an important ability for students to have today in facing the challenges of dynamic educational development. The purpose of this study was to determine the effectiveness of the Project Based Learning (PjBL) model on student creativity in developing mathematics learning innovations. The subjects of this research were students of the Mathematics Education study program class 3A who were taking the Teaching and Learning course. The research method used is descriptive-quantitative with steps including: 1) problem identification, 2) reviewing literature related to PjBL models and creativity, 3) collecting and analyzing data, and 4) drawing conclusions. The instruments used in this study were observation sheets and tests. The results of this study indicate that the Project Based Learning (PjBL) model is effective in increasing students' creativity in developing mathematics learning innovations. Therefore, the PjBL Model can be used as an alternative learning that can develop students' creativity in making lecture work.